Network Analysis of a Maritime Trade in Medieval Japan - Dimitri Tatoyan; Aleksandra Kobiljski; Hiroki Yamashita; Éric Mermet (Journal of Historical Network Research)
The 1445 Toll Register is the only surviving medieval customs register in Japan. As such, it is a precious window into Japan’s medieval commercial revolution. While well studied using traditional methods, this article is the first attempt to submit this source to social network analysis (SNA) methods. It highlights the potential of statistical, spatial and network analysis, producing visualizations which nuance our understanding of the role of commercial agents in the medieval maritime trade. Starting from visualizing the overall network, this article probes into the legwork of a commodity network, much of which passed through the hands of the commercial agents. Our analysis also reveals that a group of 32 actors, who in the register appear to have been principally commercial agents, were in fact also shipmasters. A community detection method allows us to open up new avenues of understanding maritime trade clusters, while geospatial data visualization point to a historically irregular absence which requires further research.